The Role of Bone Morphogenetic Protein 9 in Nonalcoholic Fatty Liver Disease in Mice - Sun, Qin-Juan; Cai, Ling-Yan; Jian, Jie; Cui, Ya-Lu; Huang, Chen-Kai; Liu, Shu-Qing; Lu, Jin-Lai; Wang, Wei; Zeng, Xin; Zhong, Lan (Frontiers in Pharmacology, 2021)
Background & Aims: It’s reported that bone morphogenetic protein 9 (BMP9) played an important role in lipid and glucose metabolism, but the role of BMP9 in nonalcoholic fatty liver disease (NAFLD) is unclear. Here, we evaluated the therapeutic efficacy of recombined BMP9 in NAFLD mice and investigated the potential mechanism. Methods: The effects of recombinant BMP9 on NAFLD were assessed in HFD-induced NAFLD mice. C57BL/6 mice were administrated with high-fat diet (HFD) for 12 weeks. In the last 4 weeks, mice were treated with PBS or recombined BMP9 once daily. Insulin sensitivity was evaluated by glucose tolerance test (GTT) and insulin tolerance test (ITT) at the end of the 12th week. Then NAFLD related indicators were accessed by a variety of biological methods, including histology, western blotting, real-time PCR, RNA-seq and assay for transposase-accessible chromatin using sequencing (ATAC-seq) analyses. Results: BMP9 reduced obesity, improved glucose metabolism, alleviated hepatic steatosis and decreased liver macrophages infiltration in HFD mice. RNA-seq showed that Cers6, Cidea, Fabp4 involved in lipid and glucose metabolism and Fos, Ccl2, Trl1 involved in inflammatory response downregulated significantly after BMP9 treatment in HFD mouse liver. ATAC-seq showed that chromatin accessibility on promoters of Cers6, Fabp4, Ccl2 and Fos decreased after BMP9 treatment in HFD mouse liver. KEGG pathway analysis of dysregulated genes in RNA-seq and integration of RNA-seq and ATAC-seq showed that TNF signaling pathway and Toll-like receptor signaling pathway decreased in BMP9 treated HFD mouse liver. Conclusions: Our data revealed that BMP9 alleviated NAFLD via improving glucose and lipid metabolism, decreasing inflammatory response and reshaping chromatin accessibility in HFD mouse liver. BMP9 downregulated genes related to lipid metabolism, glucose metabolism and inflammation expression partly via decreasing promoter chromatin accessibility of Cers6, Fabp4, Fos and Tlr1. The effect of BMP9 on NAFLD is all-round, but not only focus on lipid and glucose metabolism.